New Insight into Brucella Infection and Foodborne Diseases - Ranjbar, Mitra; Nojomi, Marzieh; Mascellino, Maria T. (IntechOpen, 2020)
Brucellosis is an important zoonotic disease. More than half a million new cases from 100 countries are reported annually to the World Health Organization (WHO). The majority of patients are living in developing countries. Brucellosis is a systemic infection with a broad clinical spectrum, ranging from an asymptomatic disease to a severe and fatal illness. Clinical and laboratory features vary widely. The main presentations are acute febrile illness, localized infection, and chronic infection. Laboratory tools for diagnosis of brucellosis include culture, serology, and polymerase chain reaction (PCR). The goal of brucellosis therapy is to control the illness and prevent complications, relapses, and sequelae. Important principles of brucellosis treatment include use of antibiotics with activity in the acidic intracellular environment, use of combination regimens, and prolonged duration of treatment. This book is the result of several months of outstanding efforts by the authors and the revision of the content by experts in the field of brucellosis. This book is a valid resource and is intended for everyone interested in infectious disease to learn the most important aspects of brucellosis.